Copper and Cadmium Toxicity to Marine Phytoplankton, Chaetoceros gracilis and Isochrysis sp. - Suratno Suratno; Rachma Puspitasari; Triyoni Purbonegoro; Dieni Mansur (Universitas Gadjah Mada, 2015)
In Copper (Cu) based antifouling (AF) paints Cu was largely used as booster biocide after organotin was banned. Cu is micronutrient which is important in photosynthesis process because Cu is an essential metal as component of enzyme and electron transport chain. But in certain dosage, Cu could be toxic to marine organism. Chaetoceros gracilis and Isochrysis sp. are dominant microalgae in aquatic ecosystem. In this study the effect of Cu and Cadmium (Cd) on two marine microalgae, C. gracilis and Isochrysis sp. were compared. Toxicity test was based on American Standard for Testing Material (ASTM). IC50-96 h of Cd as reference toxicant was 2,370 mg.L-1 for C. gracilis and 490 mg.L-1 for Isochrysis sp. IC50-96 h of Cu to growth of C. gracilis was 63.75 mg.L-1 and Isochrysis sp. was 31.80 mg.L-1. Both Cd and Cu were inhibited growth of microalgae. Based on IC50-96 h value, it could be concluded that Cu was more toxic than Cd. Toxicity of Cu was 37 times stronger than Cd for C. gracilis and 15 times for Isochrysis sp. It was estimated that at concentration 10 mg.L-1 Cu does not show observable effect (NOEC) to C. gracilis and 5 mg.L-1 to Isochrysis sp. The lowest observable effect of Cu (LOEC) to C. gracilis was at concentration 17 mg.L-1 and 10 mg.L-1 for Isochrysis sp.